Analysis of Problem Presentation of PBL Model on Grade VII Social Teacher - Prastiwi, Ana; Pramono, Suwito Eko; Suhandini, Purwadi (Universitas Negeri Semarang, 2019)
The PBL is more appropriately applied to social studies material that contains social problems. The teacher as a facilitator in implementing the PBL. But in reality, the PBL cannot be applied by all teachers and the presentation of the problem isn’t yet a real problem around the students. The research purpose was to analyze the presentation of factual problems, application of the PBL, and finding the obstacles experienced. The research method is a descriptive percentage that describes the presentation of the problem and the application. The population is ten social sciences teachers from different schools in Ungaran. The sample is a lesson plan from ten social sciences teachers in VII grade. Data obtained through observation, interviews, and documentation. The research result showed that the analysis of the problem presentation was quite good at 67%, six teachers use PBL from ten teachers, and Application of the 100% PBL according to the syntax. Constraints are the lack of willingness of teachers in determining problems, and time allocation arrangements are still inappropriate. The conclusion is that not all teachers can use the PBL, and the problem presentation is less factual. Teachers should be more active and creative in applying the PBL.